MEDIA LOKAL KETAHANAN BUDAYA NASIONAL - Herdi, Herdi (Institut Seni Budaya Indonesia Bandung, 2017)
This paper is an author's study of the role of local television media as one of the national culture resilience. Traditional arts programs are more promoted on local television than television in Jakarta which airs throughout Indonesia. National TV, TVRI is only given four hours for local broadcast. That is, from 3 pm to 7 pm. In fact, the Indonesian nation is now a soft target to always consumptive with foreign cultures and make it as a lifestyle of the younger generation.The Indonesian nation is a country which is rich in ethnic, cultural and linguistic diversity. When asked, what is the characteristic of Indonesian culture? The answer is the existing culture from Sabang to Merauke. That means Indonesian culture is stuck in the roots of the entire island, be it a province, city or district that exists throughout Indonesia. That is, the resilience of national culture resides at each local level.Of the twenty-four hours of television broadcasting in Indonesia. Who diligently explore and even promote traditional art in each region? It is certain that local media and local television are keen to cover, publish and display traditional arts as national culture resilience. Of the twenty-four hours, the ration of the program content, it could be that tv in Jakarta only aired one to two hours containing the local culture as a form of national culture resilience. While in the media and local television it can be ascertained seventy to eighty percent to provide information about local wisdom and culture as a manifestation of maintaining national culture.